2019
DOI: 10.1016/j.amjmed.2018.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Internal Medicine Residency Program Director Burnout and Program Director Turnover: Results of a National Survey

Abstract: AAIM is the largest academically focused specialty organization representing departments of internal medicine at medical schools and teaching hospitals in the United States and Canada. As a consortium of five organizations, AAIM represents department chairs and chiefs; clerkship, residency, and fellowship program directors; division chiefs; and academic and business administrators as well as other faculty and staff in departments of internal medicine and their divisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 27 publications
2
34
0
Order By: Relevance
“…Program director consideration of resigning was previously shown to be strongly associated with both burnout and program director turnover. 6 Our study confirms the strong association between burnout and consideration of resigning and also demonstrates that program directors who are burned out have stronger intent to resign than those not burned out. We identified many factors affecting consideration of resigning.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Program director consideration of resigning was previously shown to be strongly associated with both burnout and program director turnover. 6 Our study confirms the strong association between burnout and consideration of resigning and also demonstrates that program directors who are burned out have stronger intent to resign than those not burned out. We identified many factors affecting consideration of resigning.…”
Section: Discussionsupporting
confidence: 82%
“…In a recent study of program director turnover, we found strong associations between turnover and consideration of resigning (hazard ratio [HR] 4.05) and between turnover and burnout (HR 1.89); notably, nearly one-half of program directors had considered resigning in the preceding year. 6 This study seeks to assess intent to resign and reasons associated with why program directors consider resigning.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, burnout could affect the quality of life of these program directors, and ultimately the program as a whole. Evidence suggests that burnout is related to job turnover in medical residency program directors, 5 and frequent turnover in this important role can have ripple effects on the entire program.…”
mentioning
confidence: 99%
“…But more recent literature in management suggests that excess stability may be a liability, and may broadly represent stagnation or inflexibility [15]. This change in perspective is important, since PDs tend to be more senior physicians and have relatively long tenures: indeed, over 30% of Internal Medicine Residency PD’s have been in their positions for over 7 years and an equal percentage is above the age of 55 [16]. While other physicians can utilize the length of such experiences as a way to demonstrate and advance their expert power base in clinical medicine [12], that approach may not be as tenable for PD’s.…”
Section: Main Textmentioning
confidence: 99%